2014
DOI: 10.2217/nnm.13.209
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Cisplatin Chemotherapy and Gold Nanorod-Mediated Hyperthermia on Ovarian Cancer Cells and Tumors

Abstract: Aim The synergistic effects of gold nanorod (GNR)-mediated mild hyperthermia (MHT; 42–43°C) and cisplatin (CP) activity was evaluated against chemoresistant SKOV3 cells in vitro and with a tumor xenograft model. Materials & methods In vitro studies were performed using CP at cytostatic concentrations (5 μM) and polyethylene glycol-stabilized GNRs, using near-infrared laser excitation for MHT. Results The amount of polyethylene glycol-GNRs used for environmental MHT was 1 μg/ml, several times lower than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 65 publications
4
22
0
Order By: Relevance
“…17 A second study demonstrated that mild hyperthermia mediated by gold nanorods could promote apoptotic signaling in cancer cells to provide synergy with cisplatin both in vitro and in vivo. 18 This finding was in agreement with a previous study that revealed synergy between nanorod-mediated hyperthermia and cisplatin. 19 Here, we aimed to expand upon this exciting field of study by demonstrating that nanoshell-mediated PTT could sensitize cancer cells to subtherapeutic doses of doxorubicin (dox).…”
Section: Introductionsupporting
confidence: 93%
“…17 A second study demonstrated that mild hyperthermia mediated by gold nanorods could promote apoptotic signaling in cancer cells to provide synergy with cisplatin both in vitro and in vivo. 18 This finding was in agreement with a previous study that revealed synergy between nanorod-mediated hyperthermia and cisplatin. 19 Here, we aimed to expand upon this exciting field of study by demonstrating that nanoshell-mediated PTT could sensitize cancer cells to subtherapeutic doses of doxorubicin (dox).…”
Section: Introductionsupporting
confidence: 93%
“…The significant increase of PTT and external MHT on the efficacy of these drugs, reported in previous publications, lends support to this explanation [11, 13, 35]. …”
Section: Resultssupporting
confidence: 70%
“…PTT is an effective method of achieving rapid elevated temperatures in targeted regions in the presence of NIR absorbing gold nanoparticles while limiting damage to normal structures. The efficacy of PTT induced moderate hyperthermia in several forms of combined therapy has been shown to be effective [34][35][36]. Experiments examining the effects of combined PTT + PCI treatment modalities are in progress.…”
Section: Combined Pci Mediated Chemotherapy and External Induced Mhtmentioning
confidence: 99%